German immigration to the Cape, with special reference to (a) the German military settlers of 1857; and (b) the German immigrants of 1858 - Schnell, E L G (Rhodes University, Faculty of Humanities, Department of History, 1952)
South Africa is a multi-racial society in more than one sense. There are the broad divisions of Colour, but in addition there are further divisions within each group. The European section is mostly of Dutch and British origin, but there are important other strains, notably the French and the German. The history of the Dutch and British sections has been written, and that of the French too, but the story of the German element is still incomplete. Preface.
Keywords: Germans -- South Africa -- Cape of Good Hope; Immigrants -- South Africa -- Cape of Good Hope; Cape of Good Hope (South Africa) -- History; Eastern Cape (South Africa) -- History